Fleksibilitas dan Inovasi di Sektor Publik - Zulkenedi Zulkenedi; Aldri Frinaldi (Cakrawala Repositori IMWI, 2023)
This paper aims to review various literatures and observe and analyze innovations in the public sector that occur in countries and regions. From the results of a review of several literatures, it turns out that there are still obstacles in developing and even implementing innovations in the public sector. This obstacle does not only occur in large conditions, for example in a country, but also in small areas, namely in an area. This reduction is basically the same. These include lack of support from immediate superiors, unsupportive systems for ideas management, poor facilities, little emphasis on dissemination and commercialization, inadequate reward and incentive systems, rigid and inefficient procedures due to working by existing rules. In fact, public service innovation activities that are effective, efficient and productive can still cause irregularities in their implementation. Starting from services that are not in accordance with community expectations. There are also deviations in service time uncertainty, cost uncertainty. In addition, the community has not been able to provide suggestions and criticisms for the services they receive. Illegal levies, disregard for the rights and dignity of service users also show irregularities in public services.